Sensitivity analysis of internal layout and coating thickness to overall cooling performances of laminated cooling configurations with surface thermal barrier coatings. (25th November 2020) - Huang, Xin; Pu, Jian; Wang, Jian-hua; Qu, Yun-feng; He, Jia-hui
Highlights: Sensitivity of internal layout to conjugate heat transfer performances was non-significant. Effect of cooling air amount on surface temperature reduction was weakened by coatings. Thicker coatings could protect more effectively metal surface. Large thermal resistance could isolate internal cooling to increase coating temperature. Coating temperature could be reduced by thin coatings coupled by 1:2:1 or 1:6:1 internal layouts. Abstract: Laminated cooling coupled by surface thermal barrier coating ( TBC ) has a large potential to provide the effective protection to components in next-generation gas turbines. However, the conjugate heat transfer characteristics of coupling system is reported rarely. In this work, the combined effects of internal element layout, coating thickness and cooling air amount on the metal and TBC surface temperatures were discussed. The conjugate heat transfer experiments were conducted under engine-similar hot-side Biot ( Bi ) numbers and mainstream-to-coolant temperature ratio, and thus, a low conductivity material was applied to simulate the actual TBC . Four TBC thicknesses could cause BiTBC / BiMetal  = 1.5, 3.0, 4.5 and 6.0 in the actual operating range. The results revealed the TBC s with BiTBC /BiMetal  ≥ 4.5 can generate a large thermal resistance to reduce the metal temperature and hence a 50% increment in metal overall cooling effectiveness. However, the dominated internal cooling was also isolated to cause an increase of exterior surface temperature of entire cooling scheme, and a significant reduction of cooling air effect. The surface temperature variations were affected by the internal layout, when adopting the TBC s with BiTBC /BiMetal  ≤ 3.0. Relative to the coolant amount and TBC thickness, the sensitivities of cooling effectiveness with internal layout were non-significant.